Low Carbon Agriculture Plan (ABC): a bibliometric review focused on the state of Mato Grosso, Brazil (Research, Society and Development, 2019)
Since the beginning of international conventions to deal with climate issues, several debates and efforts have been made to mitigate environmental impacts in the world. Among the various plans in Brazil, the Low Carbon Agriculture Plan - ABC Plan was created, which aims to reduce greenhouse gas emissions in agriculture. Thus, to describe some characteristics of the scientific productions related to the Plan and the ABC Program, in a context focused on the state of Mato Grosso, Brazil. The study was developed by means of a bibliometric survey, besides analyzing the scientific activity and identifying the trends of publications with this theme. To this end, a survey was conducted in the Dimensions databases and in the CAPES Periodicals Portal, considering as inclusion criteria: (i) general information on the ABC Plan; (ii) data on application and development of the ABC Plan and Program in Brazil and (iii) data on application and development of the ABC Plan and Program in the state of Mato Grosso, between 2014 and 2018, in Portuguese and English. Documents and monographs were excluded. The results indicated that, in 2016, there was an increase in agricultural productivity associated with the low emission of Greenhouse Gases (GHG), concomitantly with an increase in investments in the ABC Plan in Mato Grosso, showing a growing increase in scientific production of this theme. Finally, with the review, it is evident that the incentives to the ABC Plan were relevant, however, it still does not have representation for the state's agricultural production, due to the concentration of resources.